Mastering competencies in family therapy a practical approach to theories and clinical case documentation - Gehart, Diane R. 1969- (Mastering competencies series, 2018)
"Mastering Competencies In Family Therapy: A Practical Approach To Theory And Clinical Case Documentation, 3rd Edition provides a competency-based approach that introduces couple and family therapy theories while simultaneously teaching you how to complete clinical documentation. Using a light and inviting tone, Diane R. Gehart provides detailed instructions and examples that enable you to complete real-world clinical forms, which are incorporated into the text. Diversity and research considerations are integrated into theoretical discussions and practical applications to facilitate a more holistic and nuanced understanding of couple and family therapy"--Provided by publisher.